2018
DOI: 10.1111/jcpp.13004
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Maternal antidepressant use during pregnancy and offspring neurodevelopmental problems – a critical review and recommendations for future research

Abstract: Children of women treated with antidepressants during pregnancy are more likely to develop neurodevelopmental problems than are unexposed children. Associations between prenatal antidepressant exposure and neurodevelopmental problems could reflect a causal effect or could be partially or fully explained by other factors that differ between exposed and unexposed offspring, including having mothers with conditions requiring antidepressant treatment (e.g. depression), environmental risk factors, and/or genetic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 147 publications
1
51
0
Order By: Relevance
“…However, the wide‐spread SSRI effects were less expected. The use of antidepressants medication during pregnancy is thought to be relatively safe (Sujan, Öberg, Quinn, & D'Onofrio, 2019), but the topic is heavily debated (Talati & Weissman, 2019), with some reports showing increased risks for speech and language disorders in childhood (Brown et al, 2016), mood disorders in early adolescence (Brown et al, 2016), and other nonpsychiatric conditions (Gingrich et al, 2017). The topic is further complicated by the fact that maternal depression, the treatment target of SSRI, itself is linked to adverse neurodevelopmental outcomes (Lebel et al, 2016; Posner et al, 2016; Qiu et al, 2015; Rifkin‐Graboi et al, 2013; Wonch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the wide‐spread SSRI effects were less expected. The use of antidepressants medication during pregnancy is thought to be relatively safe (Sujan, Öberg, Quinn, & D'Onofrio, 2019), but the topic is heavily debated (Talati & Weissman, 2019), with some reports showing increased risks for speech and language disorders in childhood (Brown et al, 2016), mood disorders in early adolescence (Brown et al, 2016), and other nonpsychiatric conditions (Gingrich et al, 2017). The topic is further complicated by the fact that maternal depression, the treatment target of SSRI, itself is linked to adverse neurodevelopmental outcomes (Lebel et al, 2016; Posner et al, 2016; Qiu et al, 2015; Rifkin‐Graboi et al, 2013; Wonch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerably less evidence on longer‐term neurodevelopmental outcomes, but an emerging consensus that findings from preclinical (animal) studies may not apply to the human population 127 . For example, an initially concerning safety signal of an association between in utero exposure to SSRIs and autism spectrum disorder 128 is not supported by more recent, better quality evidence that takes into account confounding by underlying illness and familial variables 125,129 .…”
Section: Interventionsmentioning
confidence: 99%
“…While risk for ADHD and ASD may not be increased with fetal SSRI in utero exposure, there is other evidence that SSRI exposure may increase the risk for other problems including certain speech and language disorders in childhood (Brown et al., ), mood disorders in early adolescence (Malm et al., ), and a host of non‐psychiatric conditions (see Gingrich et al., for review) beyond the risks associated with prenatal exposure to maternal depression itself. While we applaud the Sujan et al. review and agree that the evidence for the effects of SSRI in utero exposure for ASD and ADHD is equivocal, we argue that recommendations for antidepressant use during pregnancy must take into account other potential damaging effects on the offspring or other psychiatric or non‐psychiatric complications. Effective treatment decisions require evaluation of a fuller portfolio of potential risks and benefits to the mother‐child dyad in the context of the severity of the mother's symptoms.…”
Section: Implications For Clinical Practicementioning
confidence: 91%
“…Sujan et al. provide an elegant summary of the value and limitation of animal studies. Their conclusion is that most rodent studies have found effects of perinatal antidepressant exposure on neuronal brain and behavior indices related to neurodevelopmental problems.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation